Edukasi kesehatan reproduksi melalui influencer media sosial terhadap emosi positif dan kepercayaan diri remaja - Syamson, Meriem Meisyaroh; Murtini, Murtini; Herikza, Ramli; Khotimah, Husnul; Nurdin, Nasrayanti (Holistik Jurnal Kesehatan, 2025)
Background: Adolescents often experience confusion, anxiety, and social pressure related to the physical and emotional changes that occur during puberty. Low self-confidence and a lack of positive emotions in dealing with these changes can make them vulnerable to unhealthy decision-making, including regarding sexual behavior. Reproductive education that does not address these psychological aspects is less effective in fostering healthy reproductive behaviors. Therefore, a reproductive education approach is needed that is not only informative but also able to increase positive emotions and self-confidence in adolescents to prepare them for the challenges of adolescence. Purpose: To analyze the impact of reproductive health education through social media influencers on adolescents' positive emotions and self-confidence. Method: This quantitative study used a two-group quasi-experimental design and research instruments such as surveys, interviews, and social media content analysis. Data collection included identifying influencers active in reproductive health education, observing uploaded content, and surveying adolescents in the influencers' audiences. Data analysis used paired t-tests and independent t-tests. Results: In the post-test, the health education variable for the intervention group obtained a p-value of 0.000 and a p-value of 0.013 for the control group, indicating similar differences. However, the positive emotion variable for the intervention group was 0.000, while the control group had a p-value of 0.280. This indicates a difference between the intervention group before and after the intervention, while there was no difference between the control group. Similarly, the self-confidence variable for the intervention group obtained a p-value of 0.000 and the control group a p-value of 0.569, indicating a difference between the intervention and control groups. Conclusion: There was a pre- and post-intervention effect of adolescent reproductive health education in the intervention group, while there was no difference or effect pre- and post-intervention in the control group.   Keywords: Reproductive Health Education; Positive Emotions; Influencers; Self-Confidence; Adolescents.   Pendahuluan: Remaja sering mengalami kebingungan, kecemasan, dan tekanan sosial terkait perubahan fisik dan emosional yang terjadi selama masa pubertas. Rendahnya kepercayaan diri dan kurangnya emosi positif dalam menghadapi perubahan tersebut dapat membuat mereka rentan terhadap pengambilan keputusan yang tidak sehat, termasuk dalam hal perilaku seksual. Edukasi reproduksi yang tidak menyentuh aspek psikologis ini menjadi kurang efektif dalam membentuk perilaku reproduksi yang sehat. Oleh karena itu, perlu adanya pendekatan edukasi reproduksi yang tidak hanya informatif tetapi juga mampu meningkatkan emosi positif dan kepercayaan diri remaja sebagai bekal menghadapi tantangan masa remaja. Tujuan: Untuk menganalisis edukasi kesehatan reproduksi melalui influencer media sosial terhadap emosi positif dan kepercayaan diri remaja. Metode: Penelitian kuantitatif dengan desain eksperimen (quasi-experimental design) two grup dan instrumen penelitian seperti survei, wawancara atau analisis konten media sosial. Pengumpulan data identifikasi influencer yang aktif edukasi kesehatan reproduksi, mengamati konten yang diunggah, survei remaja yang menjadi audiens influencer. Analisis data menggunakan statistic paired t test dan independent t-test. Hasil: Ketika post-test, variabel edukasi kesehatan kelompok intervensi mendapatkan p-value sebesar 0.000 dan kelompok kontrol sebesar 0.013, nilai tersebut tidak jauh berbeda. Namun, pada variabel emosi positif kelompok intervensi sebesar 0.000 sedangkan kontrol sebesar 0.280, sehingga kelompok intervensi ada perbedaan sebelum dan sesudah dilakukan intervensi, sedangkan kontrol tidak ada. Begitupun pada variabel kepercayaan diri, pada kelompok intervensi didapatkan p-value sebesar 0.000 dan kontrol sebesar 0.569, sehingga kelompok intervensi ada perbedaan, sedangkan kontrol tidak ada. Simpulan: Ada pengaruh sebelum dan sesudah dilaksanakan edukasi kesehatan reproduksi remaja pada kelompok intervensi, sedangkan kelompok kontrol tidak ada perbedaan atau pengaruh sebelum dan sesudah.   Kata Kunci: Edukasi Kesehatan Reproduksi; Emosi Positif; Influencer; Kepercayaan Diri; Remaja.